Dynamique Des Eléments Nutritifs Et Du Phytoplancton Dans Le Barrage Béni Haroun Dans l’Est Algérien - Kherief Nacereddine S.; Djeddi H.; Benayache N. Y.; Afri-Mehennaoui F. Z. (European Scientific Journal, ESJ, 2018)
In order to monitor the water quality of the Beni Haroun dam, used for the drinking water production, our research work aims to provide new scientific data on the phytoplankton population of the dam. This contribution is a qualitative and quantitative investigation of this important link in the ecosystem equilibrium. To our knowledge, this study has never been the subject of a previous one, despite many works already done on this dam. Water samples were collected monthly from January to December 2015 at five stations, spread over Beni Haroun dam. The exploitation of a database, relating to fourteen physicochemical and biotic variables, made it possible to determine: the spatiotemporal evolution of each variable, the correlations between variables, the annual variability of the algal biomass, the diversity and phytoplankton dominance.